2021
DOI: 10.3390/pharmaceutics13060824
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin-Loaded Polymeric Films for Drug Delivery Systems: Comparison between Soaking and Supercritical CO2 Impregnation

Abstract: Polymeric implants loaded with drugs can overcome the disadvantages of oral or injection drug administration and deliver the drug locally. Several methods can load drugs into polymers. Herein, soaking and supercritical CO2 (scCO2) impregnation methods were employed to load aspirin into poly(l-lactic acid) (PLLA) and linear low-density polyethylene (LLDPE). Higher drug loadings (DL) were achieved with scCO2 impregnation compared to soaking and in a shorter time (3.4 ± 0.8 vs. 1.3 ± 0.4% for PLLA; and 0.4 ± 0.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…They observed an increase in the swelling degree at higher pressures and temperatures as a result of the higher scCO 2 density and solvent diffusivity. Coutinho et al measured a swelling degree of 14% for PLLA and 6% for LLDPE films using scCO 2 at 80 °C and 300 bar after 3 h. The differences were attributed to the presence of ester groups in PLLA that can interact with CO 2 , increasing the chain mobility and swelling [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They observed an increase in the swelling degree at higher pressures and temperatures as a result of the higher scCO 2 density and solvent diffusivity. Coutinho et al measured a swelling degree of 14% for PLLA and 6% for LLDPE films using scCO 2 at 80 °C and 300 bar after 3 h. The differences were attributed to the presence of ester groups in PLLA that can interact with CO 2 , increasing the chain mobility and swelling [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…PLA is a synthetic biopolymer belonging to the family of aliphatic polyesters that has been extensively used for the supercritical impregnation of bioactive compounds [ 12 ]. PLA foams have been employed for the supercritical impregnation of cinnamaldehyde [ 13 ], and thymol [ 14 , 15 ]; it was also employed for the loading of aspirin in film form [ 16 ] and as a particle it was used for nitrendipine [ 17 ], ketoprofen and carvone [ 18 ], diclofenac [ 19 ], dihydroquercetin and α-tocopheryl succinate [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…This technique can improve polymer impregnation due to the low viscosity and good transport properties of sc-CO 2 as well as the high solvent power shown to organic molecules at moderate temperatures [ 4 , 126 ]. For instance, Trindade Coutinho et al [ 128 ] reported that the SSI process of 3 h enabled 2.6 times higher drug loading into PLA film compared with the conventional soaking method that lasted 10 days. An additional advantage of SSI is that the BCs’ load and distribution through a polymer matrix can be easily tuned by changing the process conditions [ 15 , 25 , 129 ].…”
Section: Pla Impregnation With Bioactive Components Using Sc-comentioning
confidence: 99%
“…PLA materials impregnated with BCs by sc-CO 2 can be used for the preparation of drug delivery systems [ 66 , 133 ]. For instance, PLA was impregnated with aspirin used as an anti-inflammatory drug [ 128 ], triflusal used in the prevention of cardiovascular events [ 66 ], and paclitaxel used in cancer therapy [ 124 ]. In addition, sc-CO 2 has been widely used for the preparation of bioactive medical devices such as intraocular lenses, sutures, and scaffolds for tissue engineering.…”
Section: Pla Impregnation With Bioactive Components Using Sc-comentioning
confidence: 99%
“…This parameter is highly useful since it indicates the type of release mechanism involved. For polymeric delivery systems characterized by a slab geometry, if n ≤ 0.5, a Fickian diffusion is observed, and this suggests that the drug diffuses through the hydrogel matrix [ 52 , 53 ]. In the other cases, if n = 1.0, the release is referred to as Case-II transport caused by system swelling, while if 0.5 < n < 1.0, the mechanism indicates an anomalous transport corresponding to a superposition of both diffusion and polymer relaxation.…”
Section: Resultsmentioning
confidence: 99%